Comparison of indices to estimate heat exposure to human: a review in tropical regions - Nurhartonosuro, Imam Munajat; Mohd Tamrin, Shamsul Bahri; Mohd Suadi Nata, Dayana Hazwani; Karuppiah, Karmegam; Ng, Yee Guan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Workplaces in tropical countries are associated with increasing temperature and humidity, thus, the workers are susceptible to heat hazards. The inability for self-cooling properly toward exposure to head hazards can lead to severe dehydration and even death. To date, there are several indices and models to assess heat stress, such as WBGT, ISO 7933, discomfort index, HIS, PhSI, etc. However, their accuracy and suitability for tropical regions are still under investigation since they are mostly developed for subtropical regions. This review assessed the indices to estimate heat exposure in tropical regions based on the various online database. Among those indices, WBGT is the most suitable despite its inability to estimate human thermal response in tropical regions with several adjustments. Based on this review, it showed that there is a need for improvement of current indexes to be used in tropical regions since they are more suitable for the subtropical countries.